THE RELATIONSHIP BETWEEN WOMEN’S EDUCATION AND HUMAN DEVELOPMENT - Mohammad Javad Razmi; Mohammad Ali Falahi; Ezatollah Abbasian; Marjan Salehifard (European Scientific Journal, ESJ, 2015)
The main purpose of this paper is to study the relationship between Women’s Education in primary, secondary and higher education and human development level. This relationship is studied in three groups of countries with high, medium and low human development during the period 2000-2009. The results, based on panel data model estimates show that in countries with high human development, higher educated women have more effective role in human development index. However, in countries with medium human development, secondary education of women has led to increased human development index. In countries with low human development level, all levels of education are conductive to improve the level of human development.